Sustainability and business ethics: the trend in the past 16 years/ Jen Ling Gan and Manimekalai Jambulingam - Gan, Jen Ling; Jambulingam, Manimekalai (Universiti Teknologi Mara Selangor, 2022)
The purpose of the study is to evaluate global research in form of bibliometric analysis of business ethics and its growth of publications from 2004 to 2020 from Scopus database. The study revealed, the research details such as coauthorship, leading countries in the research, top scholars and leading key words of business ethics related studies. The study contributed insights of business ethics related areas to the academics for further research. This study used VOS Viewer to analyze and visualize the global research trend on 'Sustainability in Business Ethics' in analyzing the bibliographic data. Bibliometric maps were retrieved from VOS Viewer. This paper can be beneficial for academicians, organizations, and business policymakers in understanding the global trend of 'Sustainability in Business Ethics' besides discovering the future directions and opportunities for future studies.